Risk factors for prevalence of retinopathy of prematurity in a tertiary care centre of North India - Mamta Choudhary; Nisha Dulani; Meghna Solanki; Harish Dulani (Journal of Applied Pharmaceutical Research, 2023)
Background: The goal of the current study was to shed light on the risk factors responsible for the prevalance of ROP in infants born before 34 weeks of gestation or in infants born with birth weights under 2000 g admitted in NICU at a tertiary care hospital. Methods: This study was a hospital based prospective observational study conducted on 160 neonates after ethical clearance within a period of four months. The study population comprised of neonates less than 34 week of gestational age and with birth weight less than 2000 gm and gestational age between 34-36 weeks. All statistical analysis was done using appropriate statistical software like SPSS (Statistical Sciences Package for Social). Categorical / Nominal variables were indicated as number and percentage and were surveyed using Chi square test or Fischer exact test. Continuous variables were expressed as mean and standard deviation. Results: Among the 160 neonates screened, 30 neonates were found to have Retinopathy of prematurity, giving a rate of 18.8% for ROP. Among the 30 neonates with ROP, 10 (33.3%) delivered at gestational age <32 weeks, 12 (40%) had respiratory distress syndrome, 19 (63.3%) had sepsis, 23 (76.7%) required oxygen therapy, 5 (16.7%) received mechanical ventilation, 18 (60%) received blood transfusion, 17 (56.7%) had hypoglycemia. Other risk factors have been discussed in detail in the article. Conclusion: Prematurity, low birth weight, inadvertent use of oxygen therapy blood transfusion, sepsis and hypoglycemia were found to be significant risk factor for ROP.